2012
DOI: 10.4141/cjss2011-046
|View full text |Cite
|
Sign up to set email alerts
|

Chloride leaching in two Ontario soils: Measurement and prediction using HYDRUS-1D

Abstract: Saso, J. K., Parkin, G. W., Drury, C. F., Lauzon, J. D. and Reynolds, W. D. 2012. Chloride leaching in two Ontario soils: Measurement and prediction using HYDRUS-1D. Can. J. Soil Sci. 92: 285–296. Deterministic numerical modelling can often be used to complement and extend field results, and to provide extra insight into the mechanisms of water and solute movement within the profile of agricultural soils. Chloride leaching and near-surface soil water content in a Guelph loam and a Maryhill loam cropped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The soil data was analysed statistically using one-way ANOVA followed by Duncan's test (P<0.05). Five statistical procedures (Appendix F) were used to assess the level of agreement between the predicted and observed data (to validate the model): The root mean square error (RMSE) (Legates and McCabe 1999;Saso et al 2012;Zeng et al 2014), the Nash-Sutcliffe coefficient (NSE) (Nash andSutcliffe 1970, Zeng et al 2014), the index of agreement (d) (Willmott 1981), and for the solute transport simulations the mean absolute error (MAE) and relative error (RE). The model is more accurate when the RMSE or MAE is close to zero, or the NSE or d approach one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil data was analysed statistically using one-way ANOVA followed by Duncan's test (P<0.05). Five statistical procedures (Appendix F) were used to assess the level of agreement between the predicted and observed data (to validate the model): The root mean square error (RMSE) (Legates and McCabe 1999;Saso et al 2012;Zeng et al 2014), the Nash-Sutcliffe coefficient (NSE) (Nash andSutcliffe 1970, Zeng et al 2014), the index of agreement (d) (Willmott 1981), and for the solute transport simulations the mean absolute error (MAE) and relative error (RE). The model is more accurate when the RMSE or MAE is close to zero, or the NSE or d approach one.…”
Section: Discussionmentioning
confidence: 99%
“…The advective-dispersive chemical transport under transient flow conditions in partially saturated soil (Suarez and Šimůnek 1996;Šimůnek et al 2013) was used in the model. The model's temporal and spatial discretizations were calculated by the Crank-Nicholson Scheme and Galerkin finite element schemes, respectively as described in Saso et al (2012) and Šimůnek et al (2013). The measured Gapon selectivity coefficients describing the partitioning between the solid phase and solution are listed in Tables 2-4.…”
Section: Validation Of Hydrus-1d Modelmentioning
confidence: 99%
“…Application of chloride‐containing fertilizers can increase the Cl – concentration in the soil; however, Cl – ions are more mobile in soil solution and easily leached (Saso, Parkin, Drury, Lauzon, & Reynolds, ; Shen et al., ). In the present study, soil Cl – concentrations increased with increasing chlorine levels within 1 yr of application.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the low retention of the chloride ion (Cl − ) by the binding sites present in clays and soil organic matter particles, the buildup of soil Cl over time is nearly impossible (Liu et al., 2021). Field measurements and prediction in two Canadian soils indicated that over 70% of the applied Cl can be lost to deep drainage (below 80‐cm depth) during the winter months, November to April (Saso et al., 2012). Therefore, Cl leaching below from the root uptake zone is very rapid, particularly in sandy soils after high rainfall volumes (Moore et al., 2011).…”
Section: Introductionmentioning
confidence: 99%